Resistance of yeast to inhibitors of lignocellulosic bioethanol production - Moreno-Martínez, Elena (2019)
As we witness the depletion of natural fossil fuel resources, there is an increasing urgency to find and develop sustainable alternatives that can still meet the world’s ever growing needs. Lignocellulose is one of the most abundant sources for biomass-based energy, a promising candidate for a potentially powerful new combustible. Considerable effort has been made to obtain biofuel from lignocellulosic materials using microorganisms, but there are still a number of constraints to be overcome for this new sustainable form of energy to become the ultimate solution to the petroleum problem. Upon breakdown of lignocellulosic biomass to release the sugars that will be used by the ethanologenic organisms, numerous toxic compounds are also generated; weak acids, furans and phenols impair microbial growth and fermentation, thus reducing efficiency of the process and increasing the cost.